1988
DOI: 10.1128/mcb.8.12.5513
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin structure at the promoter of a glyceraldehyde phosphate dehydrogenase gene from Saccharomyces cerevisiae reflects its functional state.

Abstract: The chromatin structure of TDH3, one of three genes encoding glyceraldehyde phosphate dehydrogenases in Saccharomyces cerevisiae, was analyzed by nuclease digestion. A large hypersensitive region was found at the TDH3 promoter extending from the RNA initiation site at position -40 to position -560. This hypersensitive domain is nucleosome free and includes all putative cis-acting regulatory DNA elements. It is equally present in cells grown on fermentable as well as nonfermentable carbon sources. In a mutant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…In this regard, phased nucleosomes were detected within the 5' regulatory sequences of the yeast glyceraldehyde-3-phosphate dehydrogenase gene TDH3 in strains carrying a gcrl null mutation. These same regulatory sequences were devoid of nucleosomes in a strain carrying the wild-type GCR1 allele (44). We suggest that GCR1 plays a role in a hierarchy of binding events leading to transcriptional activation of EN02.…”
Section: Discussionmentioning
confidence: 69%
“…In this regard, phased nucleosomes were detected within the 5' regulatory sequences of the yeast glyceraldehyde-3-phosphate dehydrogenase gene TDH3 in strains carrying a gcrl null mutation. These same regulatory sequences were devoid of nucleosomes in a strain carrying the wild-type GCR1 allele (44). We suggest that GCR1 plays a role in a hierarchy of binding events leading to transcriptional activation of EN02.…”
Section: Discussionmentioning
confidence: 69%
“…In several derivatives, transcription from both the his3 and pet56 promoters was virtually eliminated yet HinfI cleavage at the Gcn4 site occurred at a level comparable to that of the wildtype chromosomal locus. In a similar vein, Swi-Snf-or activator-dependent alterations of chromatin structure (1,7,12,29,33,46) or nuclease hypersensitivity (23,39) can occur in the absence of a functional TATA element and transcriptional activity of the promoter.…”
Section: Discussionmentioning
confidence: 99%
“…First, yeast promoters often contain transcription-independent regions of nuclease hypersensitivity (6,7,18,23,25,27,33,39,46). Second, in several of these studies, micrococcal-nuclease mapping suggests that hypersensitivity reflects "nucleosomefree" regions, although it is unclear whether these regions are truly devoid of nucleosomes or have an alternative structure.…”
mentioning
confidence: 99%
“…Pavlovic' and Horz (16) showed that chromatin structure within the 5'-flanking region of the yeast glyceraldehyde-3-phosphate dehydrogenase gene TDH3 is dependent on the GCRI gene. In GCR1+ strains, the upstream regulatory region of TDH3 is devoid of nucleosomes.…”
Section: Discussionmentioning
confidence: 99%